Investigating strangeness enhancement in jet and medium via 𝜙⁡(1020) production in 𝑝-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Menzel, Marius; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; Schlepper, Felix; et al. (Physical review, 2024)
This work aims to differentiate strangeness produced from hard processes (jetlike) and softer processes (underlying event) by measuring the angular correlation between a high-momentum trigger hadron (ℎ) acting as a jet proxy and a produced strange hadron [𝜙⁡(1020) meson]. Measuring ℎ−𝜙 correlations at midrapidity in 𝑝-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV as a function of event multiplicity provides insight into the microscopic origin of strangeness enhancement in small collision systems. The jetlike and the underlying-event-like strangeness production are investigated as a function of event multiplicity. They are also compared between a lower and higher momentum region. The evolutions of the per-trigger yields within the near-side (aligned with the trigger hadron) and away-side (in the opposite direction of the trigger hadron) jets are studied separately, allowing for the characterization of two distinct jetlike production regimes. Furthermore, the ℎ−𝜙 correlations within the underlying event give access to a production regime dominated by soft production processes, which can be compared directly to the in-jet production. Comparisons between ℎ−𝜙 and dihadron correlations show that the observed strangeness enhancement is largely driven by the underlying event, where the 𝜙/ℎ ratio is significantly larger than within the jet regions. As multiplicity increases, the fraction of the total 𝜙⁡(1020) yield coming from jets decreases compared to the underlying event production, leading to high-multiplicity events being dominated by the increased strangeness production from the underlying event.